2008
DOI: 10.1177/030089160809400516
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Interstitial Pneumonitis Associated with Guillain-Barré Syndrome during Administration of Adjuvant Trastuzumab

Abstract: Optimal treatment for HER2/neu-positive, node-positive early breast cancer should include the monoclonal antibody trastuzumab. This relatively new agent has shown very limited pulmonary toxicity. Our report describes a case of life-threatening interstitial pneumonitis associated with Guillain-Barré syndrome that occurred during the administration of adjuvant trastuzumab. The severity of the clinical presentation and the limited number of reports in the literature of acute trastuzumab-related lung injury make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Altogether, the reports of apparent trastuzumab-related pulmonary interstitial disease in B-31, N9831, and four other reports [55,[64][65][66] are highly suggestive that this syndrome is a rare, but real, complication of this therapy. In one case, the patient subsequently developed Guillian-Barre syndrome [66].…”
Section: Mechanism Of Actionmentioning
confidence: 85%
See 1 more Smart Citation
“…Altogether, the reports of apparent trastuzumab-related pulmonary interstitial disease in B-31, N9831, and four other reports [55,[64][65][66] are highly suggestive that this syndrome is a rare, but real, complication of this therapy. In one case, the patient subsequently developed Guillian-Barre syndrome [66].…”
Section: Mechanism Of Actionmentioning
confidence: 85%
“…In one case, the patient subsequently developed Guillian-Barre syndrome [66]. Clinicians should be aware of it and be prepared to respond appropriately, including discontinuation of further treatment or cautious coadministration with corticosteroids [64].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Those case reports mostly concluded that paclitaxel or docetaxel, rather than trastuzumab, was responsible for the development of ILD, as ILD is a well-known complication of taxanes. However, according to our literature survey, there have been 4 English-language case reports of trastuzumab monotherapy-associated ILD (10)(11)(12)(13). Those cases and the 3 cases presented herein are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cases of subacute interstitial lung disease (ILD), organizing pneumonia and acute respiratory distress syndrome, have been reported in patients on trastuzumab treatment (incidence ≤1%). [6][7][8] Taxaneinduced pneumonitis has also been reported in a few case reports, with an incidence rate of about 5%. 9 Although the pulmonary toxicity induced by trastuzumab is rare, it can be life-threatening.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 85%